ESTIMASI POTENSI PENYERAPAN KARBON BIRU (BLUE CARBON) OLEH HUTAN MANGROVE SULAWESI UTARA - Sondak, Calvyn F. A. (Journal of Asean Studies on Maritime Issues, 2015)
Coastal ecosystems such as mangroves, tidal marsh and seagrass beds provide many benefits and services that are essential for adaptation to climate change along the global coasts, including the sequestration and storage of carbon dioxide (CO2). Currently there is an increase of mangrove loss due to unsustainable use. Mangrove forests can absorb and store large amounts of carbon (blue carbon) from the atmosphere and ocean. As a results mangrove role on combat climate change is recognized. However when degraded, due to exploitative or land clearing, this ecosystem will be the source of greenhouse gas such as carbon dioxide. This study estimated the potential of mangrove forests in North Sulawesi to absorb and sequester CO2. Result shows that 1,169,141 t C (100 t C ha-1) and 4,290,747 t CO2eq (367.01 t CO2eq ha-1) potentially removed and sequestered by mangrove ecosystem.